Productive and technological aspects of dairy cattle from Sinop, Mato grosso, Brazil - Marcon, G. C.; Socoloski, S. N. G.; Zane, A. C.; Santos, R.; Gomes, S. C.; Castro, B. G. (Scientific Electronic Archives, 2014)
Knowledge of dairy productive and technological aspects is extremely important to draw a profile of milk production, detect failures to project public politics to support dairy farmers. According to the answers collected by a epidemiological enquire in 25 dairy farms in Sinop, Mato Grosso, Brazil, its dairy production comes from small family farms do not have a very specialized cows, the pasture is the main food source used and the daily individual average production per cow Â is 10.12 L.